Sleep disturbance and incident Alzheimer's disease: A UK Biobank study of 502, 538 middle‐aged to older participants: Biomarkers (non‐neuroimaging): Alzheimer's disease incidence, risk factors and biomarkers. (7th December 2020) - Gao, Lei; Li, Peng; Cui, Longcong; Wong, Patricia M; Johnson‐Akeju, Oluwaseun; Lane, Jacqueline; Saxena, Richa; Scheer, Frank; Hu, Kun
Abstract: Background: Recent cross‐sectional studies have suggested a link between sleep disturbance and worse neurocognitive function. We hypothesized that sleep disturbance traits (short/long habitual sleep duration, insomnia, daytime somnolence, and napping), and sleep apnea were linked to the development of incident Alzheimer's disease (AD) in a large, prospective cohort spanning over a decade. Method: We studied 502, 538 participants from the UK Biobank, free from AD at baseline (mean age 57, range: 37‐73), who have been followed for up to 12 years. AD date of diagnosis was obtained through algorithmic combinations of coded information from hospital admissions (diagnoses and procedures) and death registries. Cox proportional hazards models were performed to examine the association between sleep disturbance with incident AD during follow‐up. Sleep disturbance traits include: self‐reported sleep duration (short <6hrs/intermediate 6‐9h/long>9h), daytime somnolence (often/rarely), napping (usually/rarely). Sleep apnea presence was derived from ICD‐10 diagnosis and/or self‐report. Our core models with individual sleep disturbance traits were adjusted for age, sex, education, and ethnicity. The full model adjusted for major comorbidities [the Townsend deprivation index ‐ a measure of socioeconomic status, body mass index, physical activity, major cardiovascular diseases and risk factors (hypertension, high cholesterol, smoking, diabetes, AF, angina/MI, peripheral vascular disease), neurological diseases (stroke/TIA, dementia, Parkinson's), respiratory diseases (COPD, fibrosis), alcohol use, depression/anxiety, and medication use (benzodiazepines, sedatives/sleep aides, antipsychotics, steroids and opioids)]. Result: In total, 932 developed AD after 6.4 years (SD=1.9). In our full model, long habitual sleep (>9h), but not short sleep (<6h), saw a two‐fold increased risk (HR 2.04, 95% CI: 1.55‐2.67 p <0.0001) compared to intermediate sleep (6‐9h) duration. Daytime somnolence was independently predictive of AD (HR 1.56, 95% CI: 1.18‐2.03, p =0.001). These effects remained after controlling for sleep apnea, which was only predictive in the core model (HR 2.05, 95% CI: 1.23‐3.42, p =0.006). Conclusion: Long habitual sleep duration and daytime somnolence may be early, independent markers of AD. Further work examining objective measures of sleep duration and sleep disturbance within this population is ongoing, and may help confirm our findings. If replicated, future trials may be warranted to test whether optimizing sleep health reduces the risk of developing AD.